Meta-Analysis at the Root of Terrorism from the Perspective of Islamic Movement in Indonesia - Dinda Rosanti Salsa Bela; Achmad Nurmandi; Isnaini Muallidin; Danang Kurniawan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
This paper aims to map the root of terrorism in Indonesia from the Islamic movement perspective. The authors want to know how the root of terrorism has strengthened in Indonesia. A qualitative method approach was taken through a literature study regarding the delivery of research map information while the data was exported in the RIS Export file format. Then, the authors exported the data and processed it using VOSviewer to find out a bibliometric map of research development based on significant themes of Indonesian terrorism cases. Nvivo 12 plus provided exploration and description of terrorism in Indonesia to get an efficient explanation of the data. The findings are, the first to map the issue of terrorism in Indonesia. First, there was a correlation between terrorism, radicalism, and Islam. Different views of religious teachings eventually led to the terrorism movement. Several radical Islamic organizations in Indonesia have portrayed Islam as a terrorist religion. Second, the factors causing the strengthening of terrorism in Indonesia were due to injustice, oppression, and discrimination leading to terrorism and radicalism using the concept of jihad. This research suggests that the government can handle terrorism cases in Indonesia and neutralize ideas that are considered radical with a de-radicalization approach. (Tulisan ini bertujuan memetakan akar terorisme di Indonesia dari aspek gerakan Islam. Penulis ingin mengetahui bagaimana akar terorisme menguat di Indonesia. Pendekatan metode kualitatif ditempuh melalui studi pustaka sedangkan untuk penyampaian informasi peta penelitian, data diekspor dalam format file Ekspor RIS. Kemudian, penulis mengekspor data dalam format (RIS), mengolahnya menggunakan VOS viewer untuk mengetahui peta bibliometrik pengembangan penelitian berdasarkan tema signifikan kasus terorisme di Indonesia dan menggunakan Nvivo 12 plus untuk memberikan eksplorasi dan deskripsi terorisme di Indonesia demi mendapatkan penjelasan yang efisien dari data. Temuan penelitian ini adalah; Pertama, pada tahap pemetaan isu terorisme di Indonesia, terdapat korelasi antara terorisme, radikalisme, dan Islam. Perbedaan pandangan terhadap ajaran agama pada akhirnya memunculkan gerakan terorisme. Beberapa organisasi Islam radikal di Indonesia telah mencitrakan Islam sebagai agama teroris. Kedua, diketahui faktor penyebab menguatnya terorisme di Indonesia adalah rasa ketidakadilan, penindasan dan diskriminasi yang berujung pada gerakan terorisme dan radikalisme dengan mengusung konsep jihad. Saran dari penelitian ini adalah agar pemerintah dapat menangani kasus terorisme di Indonesia dan menetralisir ide-ide yang dianggap radikal dengan pendekatan deradikalisasi.